2020
DOI: 10.1371/journal.pone.0232631
|View full text |Cite
|
Sign up to set email alerts
|

Does the skull Hounsfield unit predict shunt dependent hydrocephalus after decompressive craniectomy for traumatic acute subdural hematoma?

Abstract: Background and purposePosttraumatic hydrocephalus affects 11.9%-36% of patients undergoing decompressive craniectomy (DC) after traumatic brain injury and necessitates a ventriculo-peritoneal shunt placement. As bone and arachnoid trabeculae share the same collagen type, we investigated possible connections between the skull Hounsfield unit (HU) values and shunt-dependent hydrocephalus (SDHC) in patients that received cranioplasty after DC for traumatic acute subdural hematoma (SDH). MethodsWe measured HU valu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…In our study, the incidence of communicating hydrocephalus was 30.39%, which was within the range of the abovementioned incidence of traumatic hydrocephalus. DC was significantly correlated with postoperative hydrocephalus [17,18]. e reason is that, after decompressive craniectomy, the skull loses its protective effect, the volume in the skull cavity is unstable, and the normal intracranial pressure balance is destroyed, which affects the CSF pressure, deforms the ventricle, affects the hemodynamics, and finally, affects the generation and absorption of hydrocephalus [19].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our study, the incidence of communicating hydrocephalus was 30.39%, which was within the range of the abovementioned incidence of traumatic hydrocephalus. DC was significantly correlated with postoperative hydrocephalus [17,18]. e reason is that, after decompressive craniectomy, the skull loses its protective effect, the volume in the skull cavity is unstable, and the normal intracranial pressure balance is destroyed, which affects the CSF pressure, deforms the ventricle, affects the hemodynamics, and finally, affects the generation and absorption of hydrocephalus [19].…”
Section: Discussionmentioning
confidence: 99%
“…Monitoring the levels of NGF, ACTH, and AVP is of great significance for clinicians to judge the occurrence of traffic hydrocephalus, evaluate the prognosis of patients with craniocerebral injury after DC, and guide clinical treatment. [17]…”
Section: Discussionmentioning
confidence: 99%
“…Birnbaum BA et al reported that there are variations in Hounsfield values between scanners including Philips and Siemens, however this is very minute (range 0-20 HU). 36 In addition, there is the caveat of interobserver bias whilst selecting the exact points for Hounsfield measurement. To account for this bias, In Suk Bae et al recommends an oval function called 'Region of Interest (ROI)' whereby the maximum, minimum and mean HU values can be automatically obtained by the PACS system.…”
Section: Limitationsmentioning
confidence: 99%